2021
DOI: 10.3389/fgene.2021.657171
|View full text |Cite
|
Sign up to set email alerts
|

N6-Methyladenine in Eukaryotic DNA: Tissue Distribution, Early Embryo Development, and Neuronal Toxicity

Abstract: DNA methylation is one of the most important epigenetic modifications and is closely related with several biological processes such as regulation of gene transcription and the development of non-malignant diseases. The prevailing dogma states that DNA methylation in eukaryotes occurs essentially through 5-methylcytosine (5mC) but recently adenine methylation was also found to be present in eukaryotes. In mouse embryonic stem cells, 6-methyladenine (6mA) was associated with the repression and silencing of genes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 66 publications
(122 reference statements)
0
8
0
Order By: Relevance
“…Hexabromocyclododecane disrupts the thyroid system in humans and other animals, and is a substance of concern for foetuses, new-borns exposed by breastfeeding, and children exposed via food and dust ingestion (Chain et al 2021; ECHA 2019 ; Kim and Oh 2014 ). Pre-clinical early-life models confirm the toxicity of hexabromocyclododecane for the developing brain (Fernandes et al 2021 ; Maurice et al 2015 ). Epidemiological data suggest that in utero exposure to hexabromocyclododecane induces modifications in motor skills, attention span and metabolism (Roze et al 2009 ).…”
Section: Autism Spectrum Disordersmentioning
confidence: 92%
“…Hexabromocyclododecane disrupts the thyroid system in humans and other animals, and is a substance of concern for foetuses, new-borns exposed by breastfeeding, and children exposed via food and dust ingestion (Chain et al 2021; ECHA 2019 ; Kim and Oh 2014 ). Pre-clinical early-life models confirm the toxicity of hexabromocyclododecane for the developing brain (Fernandes et al 2021 ; Maurice et al 2015 ). Epidemiological data suggest that in utero exposure to hexabromocyclododecane induces modifications in motor skills, attention span and metabolism (Roze et al 2009 ).…”
Section: Autism Spectrum Disordersmentioning
confidence: 92%
“…(Wu et al, 2016). In contrast, the level of 6 mA showed a linear increase in the embryonic states of mice and zebrafish (Fernandes et al, 2021). However, another group of researchers could not detect 6 mA in mouse ESCs or other tissues, which aroused extensive discussion (Schiffers et al, 2017).…”
Section: Prevalence Of 6 Mamentioning
confidence: 99%
“…However, another study showed that the level of 6 mA presented a linear increase in the embryonic states of mice and zebrafish (Fernandes et al, 2021). In mice, 6 mA is most abundant in the lungs, spleen, and brain, especially in the prefrontal cortex (PFC); therefore, it may play an important role in regulating the development of the nervous system and may be associated with certain neurological disorders (Fernandes et al, 2021). 6 mA was also detected in mouse ESCs.…”
Section: Ma and Embryogenesismentioning
confidence: 99%
“…α-HBCDD exposure impacts various biological systems such as the thyroid axis [17], the immune system [18] and the liver [19]. These tissues are all highly vulnerable during the perinatal period, and exposure to α-HBCDD will result in long-term consequences, even at low doses [20]. The potential human toxicity of α-HBCDD has been widely established and has resulted in its recent classification as a "Substance of Very High Concern" in Annex XIV of the REACH European Regulation.…”
Section: Introductionmentioning
confidence: 99%